2019
DOI: 10.18805/lr-468
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different mixture ratios of grass pea (Lathyrus sativus L.) and barley (Hordeum vulgare) on quality of silage

Abstract: The study was aimed to determine the properties of silages obtained by growing different mixture ratios of grass pea and barley harvested in the flowering and spike period, respectively. The research was carried out in the experimental field of the GAP International Agricultural Research and Training Center during 2014-2015 and 2015-2016 growth seasons during two years. “Kendal” barley variety and GAP Mavisi grass pea variety were used as material.The treatments viz.,100% barley, 100% grass pea, 75% grass pea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 3 publications
1
4
0
5
Order By: Relevance
“…The lowest crude protein content was obtained from pure barley silage, while there was an increase in crude protein content depending on increasing vetch ration in mixture silages. Our findings regarding with crude protein achieved in this study were generally in accordance with the results reported by (Aykan and Saruhan, 2018;Bengisu, 2019;Seydosoglu, 2019).…”
Section: Dm (Dry Matter) Ratiosupporting
confidence: 93%
“…The lowest crude protein content was obtained from pure barley silage, while there was an increase in crude protein content depending on increasing vetch ration in mixture silages. Our findings regarding with crude protein achieved in this study were generally in accordance with the results reported by (Aykan and Saruhan, 2018;Bengisu, 2019;Seydosoglu, 2019).…”
Section: Dm (Dry Matter) Ratiosupporting
confidence: 93%
“…Bu da beklenen bir durumdur (Çizelge 3). Pek çok araştırıcı karışıma dâhil olan arpa miktarının artması sonucu pH değerinin düştüğünü bildirmişlerdir (Aykan ve Saruhan, 2018;Bengisu, 2019;Seydoşoğlu ve Gelir 2019;Seydoşoğlu, 2019a;Seydoşoğlu, 2019b). Veriler değerlendirildiğinde; en yüksek silaj kuru madde oranı %100 arpa silajında (%28.77), en düşük ise %100 Macar fiği silajında (%22.11) belirlendiği görülmektedir.…”
Section: Silaj Ph Değeri Km Hp Adf Ve Ndf Oranıunclassified
“…Yem bezelyesi silajında ham protein oranı %%12.10-18.75, ham kül oranı %8.21-8.38, flieg 104.20-111.50 puan olarak tespit etmiştir (Seydoşoğlu, 2019a). Mürdümük silajında ham protein oranı %22.96, ham kül oranını ise %8.50 olarak tespit etmiştir (Seydoşoğlu, 2019b).…”
Section: Araştırma Sonuçları Ve Tartışmaunclassified
“…(Seydoşoğlu, 2019a). Mürdümük silajında ham protein oranı %22.96, ham kül oranını ise %8.50 olarak tespit etmiştir (Seydoşoğlu, 2019b).…”
Section: Araştırma Sonuçları Ve Tartışmaunclassified
See 1 more Smart Citation